Bilateral agreement for the academic years 2008-2009, 2012-2013 LLP Programme between programme: higher education (Erasmus) between Università Iuav di Venezia and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Cooperate in the LLP/Erasmus activities - Subject area: Architecture, urban and regional planning.